2021
DOI: 10.7860/jcdr/2021/47463.14996
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hamstring Tightness in Young Orthopaedic Surgeons

Abstract: Introduction: Hamstring is a group of muscles that form an important part of core muscles (lumbo-pelvic and hip complex) and their tightness may reduce the lumbar lordosis thereby potentially decreasing the absorption of force, affecting posture, range of motion of lower limbs and increasing the possibility of developing Low Back Pain (LBP). It was planned to test hamstring tightness in group of Orthopaedic Surgeons as this group has been shown to be prone to develop back pain. Aim: To find prevalence of hams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…At the conclusion of screening, 34 articles were included in the present systematic review 4-9,13-40 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…At the conclusion of screening, 34 articles were included in the present systematic review 4-9,13-40 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…1). Eight studies reported on the biomechanical burden of orthopaedic procedures 13-20 , while 26 studies reported on MSK symptoms or injuries experienced by orthopaedic surgeons 4-9,21-40 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations